The adjective "vallejiano" in the Dictionary of the Spanish Language - Javier Pérez, Francisco (2018)
I would like my first words at the opening of this III International Congress Vallejo Siempre, which hosts this incomparable venue of the Casa de las Conchas, the Gothic palace of Don Rodrigo Maldonado de Talavera, to be words of gratitude to the organizing institutions and the committed creators of this event. I would like to advance what could be one of the conclusions of this congress which, although simple, is nonetheless tremendously significant. It is that you propose to the academies -and here is my suggestion- that the Dictionary of the Spanish language, whose 24th edition is currently being worked on, include the adjective "vallejiano", referring to "that which belongs to or relates to the poet César Vallejo" and to the "scholar of César Vallejo's work", which does not appear in the current edition of the most important and influential dictionary of our language. It would be, in another sense, like giving Vallejo a new form of permanence in our imagination, thanks to his stable presence in the repertoires that lexically describe Spanish. It would be like giving him a new life, making him word and standard, by the irradiation that his dictionary presence will produce in all those who tomorrow will speak our language; that powerful Spanish that the poet himself contributed so much to perfect.